Hubungan Epistemologi Keislaman Muhammad Abid Al-Jabiri dengan Tipologi Penafsiran Al-Qur’an - Hakam Al Ma'mun (Journal of Islamic Civilization, 2021)
This article examines the thoughts of Muhammad Abid Al-Jabiri, an Islamic thinker from the Maghrib region (Morocco). Abid Al-Jabiri made a classification of Islamic epistemology, namely bayani, burhani and 'Irfani.The existence of this epistemology turns out to have continuity with the treasures of al-Qur'an interpretation. To find the point of continuity, this study uses a descriptive-analytical method by elaborating the data contained in Al-Jabiri's work. Through the analysis of each epistemology and use of the Qur'an, the writer finds plans between one another. Based on the research conducted, the writer found similarities between Al-Jabiri's Islamic epistemology and the typology of the Qur'an. First, the epistemology of bayani has similarities with the typology of fiqh-style interpretation which tends to accommodate texts based on narration. Second, Burhani's epistemology finds its relevance with a philosophical-scientific typology of interpretation based on rationality. Third, the epistemology of 'irfani patron is a typology of isyari-style interpretation which is more of an esoteric aspect. The three Islamic epistemologies of Muhammad Abid Al-Jabiri form a typology of interpretation that can make it easier for interpretation scholars to have the dominance of reason that plays a role in a product of the Qur'an. Artikel ini menjelaskan pemikiran Muhammad Abid Al-Jabiri seorang pemikir Islam yang berasal dari wilayah Maghrib (Maroko). Abid Al-Jabiri membuat klasifikasi terhadap epistemologi keislaman yakni bayani, burhani dan ‘Irfani. Keberadaan epistemologi ini ternyata memiliki kesinambungan dengan khazanah tafsir al-Qur’an. Untuk mencari titik kesinambungan tersebut, maka penelitian ini menggunakan metode diskriptif-analitis dengan mengelaborasi data yang terdapat pada karya Al-Jabiri.  Melalui analisis terhadap karakteristik masing-masing epistemologi dan kecenderungan penafsiran al-Qur’an ini kemudian penulis menemukan kesesuaian antara satu dengan lainnya. Berdasarkan penelitian yang dilakukan penulis menemukan kesamaan antara epistemologi keislaman Al-Jabiri dengan tipologi penafsiran al-Qur’an. Pertama, epistemologi bayani mempunyai kesamaan dengan tipologi tafsir bercorak fiqih yang lebih cenderung mengakomodir teks-teks yang berbasis kepada periwayatan. Kedua, epistemologi burhani menemukan relevansinya dengan tipologi tafsir bercorak falsafi-saintifik yang berbasis kepada rasionalitas. Ketiga, epistemologi ‘irfani patronnya adalah tipologi tafsir bercorak isyari yang lebih mengedepankan aspek esoteris. Ketiga epistemologi keislaman Muhammad Abid Al-Jabiri tersebut membentuk tipologi tafsir yang dapat memudahkan para pengkaji tafsir untuk menandai dominasi nalar yang berperan dalam sebuah produk penafsiran al-Qur’an.